2011
DOI: 10.1111/j.1439-0507.2011.02044.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasive fungal infections in the intensive care unit: a multicentre, prospective, observational study in Italy (2006–2008)

Abstract: Critically ill patients admitted to intensive care units (ICU) are highly susceptible to healthcare-associated infections caused by fungi. A prospective sequential survey of invasive fungal infections was conducted from May 2006 to April 2008 in 38 ICUs of 27 Italian hospitals. A total of 384 fungal infections (318 invasive Candida infections, three cryptococcosis and 63 mould infections) were notified. The median rate of candidaemia was 10.08 per 1000 admissions. In 15% of cases, the infection was already pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
74
6
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 21 publications
7
74
6
1
Order By: Relevance
“…Among Candida species, Candida glabrata and Candida albicans account for about 20 and 60%, respectively, of Candida bloodstream infections (3)(4)(5). C. glabrata, a constituent of the normal human microflora, is emerging as a clinically important opportunistic fungal pathogen, as the mortality rate of up to 60% has been associated with C. glabrata infections (5)(6)(7).…”
mentioning
confidence: 99%
“…Among Candida species, Candida glabrata and Candida albicans account for about 20 and 60%, respectively, of Candida bloodstream infections (3)(4)(5). C. glabrata, a constituent of the normal human microflora, is emerging as a clinically important opportunistic fungal pathogen, as the mortality rate of up to 60% has been associated with C. glabrata infections (5)(6)(7).…”
mentioning
confidence: 99%
“…In most previous studies, A. fumigatus was the predominant species of Aspergillus from patients with IA (10,21,33,37). In our previous environmental studies A. flavus also was the most distributed species among genus Aspergillus in indoor and outdoor environment (16,17).…”
Section: Discussionmentioning
confidence: 66%
“…The mortality percentage among IA patients was 61.5%. The previous studies have shown a diverse incidence of IA in ICU patients (10,24,37). Meersseman et al (24) in a review paper presented an incidence of IA from 0.33% to 19% among ICU patients.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations